Parallel unstructured grid DSMC for the study of molecular gas dynamics in semi-conductor manufacturing - Singh, Abhinav. (2008)
Traditionally gas flow has been modelled at the macroscopic level. This model regards gas as a continuum medium and is described in terms of its macroscopic parameters, such as velocity, pressure and temperature. The Navier-Stokes equations provide an accurate description of the gas as a continuum. But the error in Navier-Stokes results becomes significant when the Knudsen number exceeds 0.1. Alternatively, gas flow can be described at the microscopic level, which recognizes the particulate nature of gas. The mathematical model at this level is the Boltzmann equation. Numerical solution of this equation is indirectly achieved through a method called Direct Simulation Monte Carlo (DSMC).